Outcomes of gamma knife treatment for solid intracranial hemangioblastomas - (:unkn) unknown (ELSEVIER SCI LTD, 2010)
The aim of this study was to examine the results of gamma knife radiosurgery for 13 patients with residual/recurrent or newly diagnosed solid hemangioblastomas. The 13 patients had 34 solid hemangioblastomas, and all patients underwent gamma knife radiosurgery. Seven patients had von Hippel-Lindau disease and six had sporadic disease. When individual lesions were considered, the overall mean dose at the tumor periphery was 15.8 Gy (range: 12-25 Gy) and the average maximum tumor dose was 31.6 Gy (range: 24-50 Gy). The mean duration of follow-up with MRI was 50.2 months. At the last follow-up evaluation, growth control was achieved for all tumors (partial remission in three tumors [8.8%] and no change in 31 tumors [91.2%]). No radiation-related complications were encountered. Our findings reinforce the view that gamma knife radiosurgery is effective and safe for the management of solid hemangioblastomas with a diameter less than 3 cm, whether they are sporadic or associated with von Hippel-Lindau disease. The high response rate and lack of any radiation-induced side-effects confirms the suitability of the doses used in the present study. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gamma knife; Hemangioblastoma; Radiosurgery; Von Hippel-Lindau disease; CENTRAL-NERVOUS-SYSTEM; HIPPEL-LINDAU-SYNDROME; STEREOTACTIC RADIOSURGERY; NATURAL-HISTORY; SURGERY